2020
DOI: 10.1177/0885328220975249
|View full text |Cite
|
Sign up to set email alerts
|

The targeted inhibition of prostate cancer by iron-based nanoparticles based on bioinformatics

Abstract: Prostate cancer is an epithelial malignant tumor of the prostate, and it is one of the malignant tumors with a high incidence of urogenital system in men. The local treatment of prostate cancer is mainly radical resection and radical radiotherapy, but they are not applicable to advanced prostate cancer. Systemic therapy mainly includes targeted therapy and immunotherapy which could cause many complications, and will affect the prognosis and quality of life of patients. It is urgent to find new treatments for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…These nanocomposites effectively inhibited the expression of SLC4A4 and demonstrated potent inhibitory effects on PCa cells in vivo and in vitro, demonstrating their potential as therapeutic strategies for the treatment of PCa. 148 In vivo studies have shown that NPs with good biocompatibility can significantly eradicate prostate tumors. GRPr-mediated photothermal thermodynamics combined with an antiapoptotic mechanism can be used to treat PCa.…”
Section: Effects Of Nanotherapy Onmentioning
confidence: 99%
See 1 more Smart Citation
“…These nanocomposites effectively inhibited the expression of SLC4A4 and demonstrated potent inhibitory effects on PCa cells in vivo and in vitro, demonstrating their potential as therapeutic strategies for the treatment of PCa. 148 In vivo studies have shown that NPs with good biocompatibility can significantly eradicate prostate tumors. GRPr-mediated photothermal thermodynamics combined with an antiapoptotic mechanism can be used to treat PCa.…”
Section: Effects Of Nanotherapy Onmentioning
confidence: 99%
“…These nanocomposites effectively inhibited the expression of SLC4A4 and demonstrated potent inhibitory effects on PCa cells in vivo and in vitro , demonstrating their potential as therapeutic strategies for the treatment of PCa. 148 …”
Section: Application Prospect Of Nanotherapy In the Pca Microenvironmentmentioning
confidence: 99%
“…7 A study revealed that QC enhances the protective effect of CVD against renal ischemia-reperfusion injury. 24 Globally, researchers have explored and reported the theranostic benefits of various novel drug delivery systems involving nanoparticles (metal or polymeric), 25,26 microspheres, 27 hydrogels, 28 nanosuspensions, 29 emulsions, 30 and lipid-based nanocarriers (NLCs). 31 Lipid-based carrier systems are one of the most explored delivery carriers now-a-days because of their biocompatibility and therefore could enhance the solubility and bioavailability of BCS class II and class IV categoric drugs.…”
Section: Introductionmentioning
confidence: 99%